To solve the system of equations using the elimination method, we have the following two equations:
- \( 2x - 3y = 14 \) \quad (Equation 1)
- \( 4x + 3y = 10 \) \quad (Equation 2)
First, let's manipulate these equations to eliminate one of the variables. Since the coefficients of \( y \) in the two equations have opposite signs, we can add the two equations directly after multiplying Equation 1 by \( 1 \) (to keep it as it is) and Equation 2 by \( 1 \) (to keep it as it is).
Step 1: Prepare to eliminate \( y \)
We can add the two equations together:
\[
(2x - 3y) + (4x + 3y) = 14 + 10
\]
Step 2: Combine the equations
This results in:
\[
2x + 4x - 3y + 3y = 14 + 10
\]
\[
6x = 24
\]
Step 3: Solve for \( x \)
Now, divide both sides by \( 6 \):
\[
x = \frac{24}{6} = 4
\]
Step 4: Substitute \( x \) back to find \( y \)
Now that we have \( x = 4 \), substitute this value back into either of the original equations. We'll use Equation 1:
\[
2(4) - 3y = 14
\]
This simplifies to:
\[
8 - 3y = 14
\]
Step 5: Solve for \( y \)
Subtract \( 8 \) from both sides:
\[
-3y = 14 - 8
\]
\[
-3y = 6
\]
Now, divide both sides by \( -3 \):
\[
y = \frac{6}{-3} = -2
\]
Final Solution
The solution to the system of equations is:
\[
(x, y) = (4, -2)
\]